THE EFFECT OF THE CULTURALLY RESPONSIVE TEACHING (CRT) APPROACH ON THE MATHEMATICS LEARNING OUTCOMES IN ELEMENTARY SCHOOL - Rifqi Asiah; Putri Zudhah Ferryka; Nela Rofisian (El Midad, 2026)
This study aims to determine the effect of the Culturally Responsive Teaching (CRT) approach on the mathematics learning outcomes of third-grade students at SDN 2 Planggu. The CRT approach is a teaching approach that emphasizes the importance of integrating students’ cultural backgrounds into the learning process. This study employed a quantitative research design with a quasi-experimental design. The sample for this study consisted of 19 third-grade students from SDN 2 Planggu as the experimental class and 20 third-grade students from SDN 1 Canan as the control class. The results of this study indicate that, based on the descriptive analysis of the experimental class, the average pretest learning outcomes were 65.65 and the posttest 86.05, meaning there was an improvement in students’ mathematics learning outcomes using the CRT approach. Based on the descriptive analysis of the control class, the average pretest score was 59.05, and the posttest score was 79.12, indicating an improvement in students’ mathematics learning outcomes using the TPACK approach. Based on the results of the Independent Samples t-Test, the significance value (Sig., two-tailed) was 0.003 < 0.05, meaning H0 is rejected, and Ha is accepted. Thus, it can be concluded that the CRT approach has an effect on students’ mathematics learning outcomes. As the average learning outcomes in the experimental using the CRT approach were 86.05, and in the control class using the TPACK approach were 79.12, this indicates that there is a difference in mathematics learning outcomes the CRT and TPACK approaches in third-grade elementary school.